AKTIVITAS ANTIBAKTERI MINYAK NILAM (Pogostemon cablin Benth) PADA BEBERAPA TINGKAT KADAR PATCHOULI ALCOHOL - Sarifah Nurjanah; Dwi Merita Rosi; Rizqi Putri Fathoni; Sudaryanto Zain; Asri Widyasant; Indira Lanti Kaya Putri (Department of Agroindustrial Technology, Bogor Agricultural University, 2019)
Patchouli oil (Pogostemon cablin Benth) contains patchouli alcohol (PA) as the main component, which has antibacterial activity. Some previous studies suspect that the antibacterial activity is caused by the content of PA. This study aims to find out the antibacterial activity of several patchouli oil fractions resulting from the fractionation process. The method used is decriptif method. The treatment given was fractionated fraction of oil with several levels of PA (fraction 2 with PA content of 25.62%, fraction 7 with PA content of 34.65% and fraction 8 with PA content of 54.49%) and the bacterias,included :Propionibacterium acnes, Staphyloccocus aureus, Staphylococcus epidermidis, Micrococcus luteus, Pseudomonas aeruginosa, Enterobacter aerogenes, Klebsiella pneumonia, and Proteus mirabilis. The antibacterial activity was conducted by measuring the zones of inhibition. The results showed that increasing levels of patchouli PA oil affected the inhibitory diameter in several types of bacteria. The higher the PA level can increase the zones of inhibition of some types of bacteria. Fraction 8 is the most effective fraction in inhibiting the growth of P. acnes, S. aureus, S. epidermidis, M. luteus as gram-positive bacteria with zones of inhibition of 23.02 mm and 13.00 mm, 24.10 mm, respectively. 31.22 mm. Whereas in P. aeruginosa, E. aerogenes, K. pneumonia, and P. mirabilis as gram negative bacteria zones of inhibition is not formed. Keywords : antibacterial activity, fractionation, patchouli oil, patchouli alcohol